A GIS-Based Methodology for Mapping and Inventorying Posidonia oceanica Beach-Casts: A Framework for Coastal Management - Elena Piscitelli; Loredana Manfra; Fabio Matano; Diego Vicinanza; Alice Rotini (Journal of Marine Science and Engineering, 2026)
Posidonia oceanica (Delile) is a Mediterranean seagrass species whose fallen leaves accumulate along shorelines, forming compact structures known as banquettes. Despite their ecological and protective functions, these deposits remain insufficiently documented across the Mediterranean and are frequently removed before the summer season due to tourism and aesthetic considerations. This study develops and tests a Geographic Information System (GIS)-based methodology for mapping and inventorying P. oceanica beach-casts across five representative pilot areas along the Italian coastline (Western Sardinia; Liguria; Northwestern Sicily; Elba and Giglio Islands, Tuscany; Gargano coast, Apulia). The approach integrates historical Google Earth imagery with spatial datasets to characterize beach-cast occurrence and persistence and to describe their distribution in relation to selected geomorphological, environmental, and anthropogenic variables. Based on historical Google Earth imagery covering approximately three decades (~1998–present), beach-casts were identified at least once on 94% of the 393 surveyed beaches, indicating that the phenomenon is widespread across the investigated areas, with permanent banquettes representing a substantial component (63%). The spatial distribution of beach-casts was also examined in relation to shoreline dynamics, beach surface type, coastal vulnerability, and beach use, providing a descriptive characterization of their environmental and anthropogenic context, while the relative influence of the considered factors requires further investigation. The resulting standardized and reproducible framework provides a basis for future monitoring and susceptibility assessments across broader coastal sectors and can support evidence-based management of P. oceanica beach-casts.

Are polylactic acid (PLA) microplastics a risk to marine organisms? Acute and chronic effects on the amphipods Gammarus aequicauda - Francesca Biandolino; Giovanni Libralato; Loredana Manfra; Alice Rotini; Ermelinda Prato (Aquatic Toxicology, 2025)

Can biodegradable plastics mitigate plastamination? Feedbacks from marine organisms - Loredana Manfra; Luisa Albarano; Alice Rotini; Francesca Biandolino; Ermelinda Prato; Federica Carraturo; Gianluca Chiaretti; Olga Faraponova; Michela Salamone; Claudia Sebbio; Antonietta Siciliano; Andrea Tornambè; et al. (Journal of Hazardous Materials, 2025)

The under-investigated plastic threat on seagrasses worldwide: a comprehensive review - Laura Ciaralli; Alice Rotini; Massimiliano Scalici; Corrado Battisti; Stefania Chiesa; Eleni Christoforou; Giovanni Libralato; Loredana Manfra (Environmental Science and Pollution Research, 2024)

Using unmanned aerial vehicles (UAVs) and machine learning techniques for the assessment of Posidonia debris and marine (plastic) litter on coastal ecosystems - Noureddine Zaaboub; Ridha Guebsi; Riadh Salah Chaouachi; Bochra Brik; Alice Rotini; Stefania Chiesa; Sante Francesco Rende; Mohamed Makhloufi; Asma Hamza; François Galgani; Monia El Bour (Regional Studies in Marine Science, 2023)

Undisturbed Posidonia oceanica meadows maintain the epiphytic bacterial community in different environments - Alice Rotini; Chiara Conte; Gidon Winters; Marlen I. Vasquez; Luciana Migliore (Environmental Science and Pollution Research, 2023)
Seagrasses harbour different and rich epiphytic bacterial communities. These microbes may establish intimate and symbiotic relationships with the seagrass plants and change according to host species, environmental conditions, and/or ecophysiological status of their seagrass host. Although Posidonia oceanica is one of the most studied seagrasses in the world, and bacteria associated with seagrasses have been studied for over a decade, P. oceanica ’s microbiome remains hitherto little explored. Here, we applied 16S rRNA amplicon sequencing to explore the microbiome associated with the leaves of P. oceanica growing in two geomorphologically different meadows (e.g. depth, substrate, and turbidity) within the Limassol Bay (Cyprus). The morphometric (leaf area, meadow density) and biochemical (pigments, total phenols) descriptors highlighted the healthy conditions of both meadows. The leaf-associated bacterial communities showed similar structure and composition in the two sites; core microbiota members were dominated by bacteria belonging to the Thalassospiraceae, Microtrichaceae, Enterobacteriaceae, Saprospiraceae, and Hyphomonadaceae families. This analogy, even under different geomorphological conditions, suggest that in the absence of disturbances, P. oceanica maintains characteristic-associated bacterial communities. This study provides a baseline for the knowledge of the P. oceanica microbiome and further supports its use as a putative seagrass descriptor.

On Caretta caretta ’s shell: first spatial analysis of micro- and macro-epibionts on the Mediterranean loggerhead sea turtle carapace - Monica Francesca Blasi; Alice Rotini; Tiziano Bacci; Monica Targusi; Giusy Bonanno Ferraro; Luca Vecchioni; Rosa Alduina; Luciana Migliore (Marine Biology Research, 2021)

Comparative toxicity of ionic and nanoparticulate zinc in the species Cymodoce truncata, Gammarus aequicauda and Paracentrotus lividus - Ermelinda Prato; Adele Fabbrocini; Giovanni Libralato; Luciana Migliore; Isabella Parlapiano; Raffaele D’Adamo; Alice Rotini; Loredana Manfra; Giusy Lofrano; Federica Carraturo; Marco Trifuoggi; Francesca Biandolino (Environmental Science and Pollution Research, 2021)
Due to the continuous development, production and consumption of nanoparticles (NPs), their release, fate and effects in marine coastal environment can represent a major concern. The aim of this study was to evaluate the toxicity of ZnO nanoparticles (ZnO NPs) and compare it to bulk ZnSO 4 on three macroinvertebrates: the isopod Cymodoce truncata (i.e. used for the first time in ecotoxicology), the amphipod Gammarus aequicauda and the sea urchin Paracentrotus lividus . This study showed concentration- and time-dependent relationships for all biological models for both ZnO NPs and ZnSO 4 . Both Zn forms elicited high toxicity to G. aequicauda and C. truncata juveniles , but ZnO NPs induced comparable responses to both species (96h-LC 50 = 0.30 and 0.37 mg/L for G. aequicauda and C. truncata , respectively; p > 0.05), while differences were found after ZnSO 4 exposure (96h-LC 50 = 0.28 and 0.63 mg/L, respectively; p < 0.05). ZnO NPs generated sub-lethal effects on P. lividu s embryos (72h-EC 50 = 0.04 (0.03, 0.05) mg/L), not significantly different from ZnSO 4 ones (72h-EC 50 = 0.06 (0.05, 0.07) mg/L). Effects of ZnO NPs were similar to existing literature data for other testing species. C. truncata can be considered as a promising new biological model in (nano)ecotoxicology. Graphical abstract

Heavy Metals in the Adriatic-Ionian Seas: A Case Study to Illustrate the Challenges in Data Management When Dealing With Regional Datasets - Maria Eugenia Molina Jack; Rigers Bakiu; Ana Castelli; Branko Čermelj; Maja Fafanđel; Christina Georgopoulou; Giordano Giorgi; Athanasia Iona; Damir Ivankovic; Martina Kralj; Elena Partescano; Alice Rotini; et al. (Frontiers in Marine Science, 2020)

Chronic sublethal effects of ZnO nanoparticles on Tigriopus fulvus (Copepoda, Harpacticoida) - Ermelinda Prato; Isabella Parlapiano; Francesca Biandolino; Alice Rotini; Loredana Manfra; Maria Teresa Berducci; Chiara Maggi; Giovanni Libralato; Luigi Paduano; Federica Carraturo; Marco Trifuoggi; Maurizio Carotenuto; et al. (Environmental Science and Pollution Research, 2020)

The Tropical Seagrass Halophila stipulacea: Reviewing What We Know From Its Native and Invasive Habitats, Alongside Identifying Knowledge Gaps - Gidon Winters; Sven Beer; Demian A. Willette; Inés G. Viana; Kelcie L. Chiquillo; Pedro Beca-Carretero; Betty Villamayor; Tomás Azcárate-García; Rachamim Shem-Tov; Bridget Mwabvu; Luciana Migliore; Alice Rotini; et al. (Frontiers in Marine Science, 2020)